Arketipe Ketaksadaran Tokoh Faris dan Inayah dalam Novel Lail wa Qudbhan Karya Najib Al-Kailani - Khair, Rahimal (Arabiyatuna: Jurnal Bahasa Arab, 2020)
This research aims to describe the psychological conflict that can impact the changes of Faris and Inayah attitudes when acting on novel Lail wa Qudbhan by Najib al-Kailani. The approach of this research is the psychology of literature that discusses of the psychology aspects of figures in the work or is called the textual approach. The theory used to study the psychology of figures in this research is Carl Gustav Jung’s psychology theory and focused on the archetypes of the character’s unconsciousness. The research method used is a qualitative method, documentation technic with descriptive analysis of data analysis. There is also the result of this study found that the cause of the change in attitude of Faris and Inayah figures is their unconscious archetype. Faris’s archetype consists of a persona obstinacy, a shadow of killing and copulation, his anima is uncontrolled emotional, a great mother who brings destruction, wise old man who advise and teach patience, and Self want freedom of life and happiness. While Inayah’s archetype consists of a persona of a happy wife, a shadow of murder an indidelity, an animus of rational and stubborn thinking, a great mother who loves, wise old man who teaches patience, and Self want freedom and happiness.